Demographic Changes in the Population of Iraq and Their Environmental, Economic and Planning Repercussions - Jassim, Salah; Oglah, Samar (Al-Adab Journal, 2024)
Iraq is witnessing many demographic changes in its population, whether in terms of size, distribution, and age composition, which casts a shadow on the reality of the residents’ lives and their quality of life, which results in a number of problems that include several axes, such as the environment and the economy, as well as the inaccuracy of the database necessary to develop future plans to solve current problems or data.The research relied on data available from official authorities in particular to reduce its severity and damage in the future, and via Ministry of Planning for different years according to the need for research or the availability of data for the period from the sixties of the twentieth century until the year 2020.The research reached a number of results, the most important of which is that the population growth rate in Iraq, despite its decline to 2.6‎%‎. During the period 2009-2020, however, the size of the population increase is still large and constitutes pressure on the economy and the environment. Iraq is negatively affected, as unemployment rates are still high, the gender gap is large, and food security is at its lowest levels.Availability and deterioration of the Iraqi environment, especially the shortage of water and encroachment on agricultural lands due to natural factors and the current problems affecting humanity, which will increase in severity in the future, are the most prominent problems due to the lack of applicable plans and solutions.